A Comparative Analysis of Standardised Threads for Use in Implants for Direct Skeletal Attachment of Limb Prosthesis: A Finite Element Analysis - Piotr Prochor; Eugeniusz Sajewicz (Applied Bionics and Biomechanics)
The aim of the research was to determine the optimal thread’s shape to be used in implants for direct skeletal attachment of limb prosthesis. In addition, by testing appropriate parameters’ modification of the suitable thread, an attempt was made to maximise its effectiveness. The analyses included three thread types described in the ISO standards: shallow, symmetrical, and asymmetrical. The obtained results suggest that shallow thread ensures the lowest equivalent and directional stress peaks generated in the bone as well as favourable stress patterns and profiles during implant loading in relation to symmetrical and asymmetrical threads. Moreover, shallow thread ensured the generation of single equivalent and directional stress peaks, while symmetrical and asymmetrical threads provided additional stress peak for equivalent as well as for each of directional peaks. Subsequently, optimisation of the shallow thread’s shape was conducted by changing two relevant thread’s parameters (flank angle and rounding arc) which influence the generated stress distribution. The highest reduction of stress peaks was obtained while reducing the rounding arc by 0.2 mm. Therefore, it can be stated that the proposed modification of the HA thread can lead to obtaining a higher biomechanical effectiveness of implants for direct skeletal attachment of limb prosthesis.